Self-perceived health of older adults in Latin America and the Caribbean: a scoping review - Hannah Kaufman; Samantha Howell; Jeni Stolow; Katherine Andrinopoulos; Philip Anglewicz; Martín Burt; Arachu Castro (Pan American Health Organization, 2023)
Objective. To systematically map the existing evidence on self-perceived health among adults aged 60 and older in Latin America and the Caribbean, describe the use of the single-item measure of self-perceived health with this population, and identify gaps in the existing literature. Methods. Following PRISMA Extension for Scoping Reviews guidelines, eight databases were searched for publications that were published between 2009 and 2019 and reported self-perceived health of adults over 60 years old in Latin America and the Caribbean. Data on study characteristics, sample characteristics, and the use and analysis of the self-perceived health measure were charted. Results. The database and secondary searches identified 516 articles. After removing duplicates and assessing titles and abstracts for inclusion, 263 full-text articles were assessed for eligibility using the inclusion criteria and an additional 89 articles were excluded. Ultimately, 174 articles were included in the scoping review. Studies included participants from 17 countries in the region, led in frequency by Brazil with 120 articles. The self-perceived health question most often included a five-category response scale (130), and response options were predominantly divided into two (86) or three (48) categories for analysis. Conclusions. Information on the health and social needs of people aged 60 and older across Latin America and the Caribbean, particularly their perceptions of health, is limited. We highlight the need to expand research throughout the region, include particularly vulnerable populations, utilize data from longitudinal and qualitative studies, and call for transparency in how questions and responses are worded and analyzed. This review serves to inform future studies, programs, and policies directed at this population.